Influence of skeletal class and facial type on nose dimensions in a Brazilian subpopulation: a CBCT study - Gomes,Amanda Farias (2021)
Abstract: Evaluating factors that may influence the nose dimensions and, therefore, contribute to the singularity of a person, is important for obtaining a precise facial reconstruction (FR) in forensic anthropology. Thus, the aim in this study was to evaluate the influence of sex, skeletal class, and facial type on nose dimensions of Brazilian individuals using cone-beam computed tomography (CBCT) scans. CBCT images of 54 males and 67 females were classified according to skeletal class (class I, II, or III) and facial type (brachycephalic, dolichocephalic and mesocephalic). Linear and angular measurements of the nose were performed using the CS 3D Imaging software. The measurements obtained for males and females were compared by one-way ANOVA. Two-way ANOVA was used to compare the measurements in the different skeletal classes and facial types. Significance level was set at 5%. All linear measurements were greater in males (p < 0.05); the angular measurements, however, did not differ between sexes (p > 0.05). Linear and angular measurements of class III males were significantly different from the other classes; the same was observed for the angular measurements in females (p < 0.05). Regarding facial types, some linear measurements were significantly greater in dolichocephalics males (p < 0.05). For females, there was no influence of facial type (p > 0.05), except for the nasal convexity angle. Nose dimensions differed in specific points among different skeletal classes and facial types, and there was sexual dimorphism in all linear nose dimensions. This information may be applicable for nose reconstructions, allowing more reliable FR.